PEMANFAATAN EKSTRAK WORTEL DAN JAHE MERAH DALAM PEMBUATAN MINUMAN BUBUK INSTAN - Sise Heralita; Raswen Efendi; Noviar Harun (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
The purpose of this study was to determine the best ratio between carrot extract and red ginger to making instant powder drinking. This study used a Completely Randomized Design (CRD) with 4 treatments and 4 replications. The treatment used for carrot extract and red ginger extract is P1 = (80% : 20%), P2 = (70% : 30%), P3 = (60% : 40%), P4 = (50% : 50%). The data obtained were analyzed statistically using ANOVA and DNMRT at the level of 5%. The results showed that the ratio of carrot extract and red ginger extract had a significant effect on water content, ash content, sensory assessment descriptively (color, aroma, and taste) and hedonic (overall assessment) but were not significantly different from antioxidant activity. The selected instant powder extract of carrot extract and red ginger extract according to chemical analysis and descriptive and hedonic sensory assessment was treatment P4 (50% carrot extract: 50% red ginger extract). This selected treatment produced instant powder of carrot extract and red ginger extract which had moisture content of 2,50%, ash content of 1,47% and antioxidant activity of 0,24 ppm. Descriptive sensory assessment is brownish orange, ginger flavored and ginger flavored. An overall assessment of instant powder of carrot extract and red ginger extract was favored by panelist.